Infected multilocular unicystic ameloblastoma involving ramus and coronoid process: A rare case report - Nikhil Saxena; Sneha H Choudhary; Sami D Aldhuwayhi; Amar Thakare (Wolters Kluwer Medknow Publications, 2020)
Ameloblastoma is a neoplasm that originates from the odontogenic epithelium. Unicystic ameloblastoma (UA) is a rare variant of ameloblastoma occurring usually in younger population. They are characterized by slow growth and are locally aggressive, with the main site of origin being the posterior portion of the mandible. Most commonly, UA appears on radiograph as a unilocular well-demarcated radiolucency present mostly in the mandibular posterior region. Here, we report a unique case of multilocular UA in a 22-year-old male patient involving the left side of whole length of the mandibular ramus and coronoid process with impacted third molar.